Perlindungan Anak Korban Tindakan Kekerasan - Apriadi Apriadi; Tomy Dwi Cahyono (SOCIETAS, 2019)
Violence against children is a national issue that is a common concern, so that the child of the victim will have to be protected by both the state and the community. This is because the child is a successor generation in both a family and a society and a nation, so it is necessary protection and coaching in the child in ensuring the development of his mental and physical and social. The purpose of this research is to know the problems and efforts in the protection of children victims of violent acts in Sumbawa district. The method used to achieve the objectives is to use a descriptive research type that describes the problem of child violence as well as protection efforts by Sumbawa District governments against victims of violent acts, and research This uses a qualitative approach. The data collection techniques consist of primary data obtained through field observation and in-depth interviews. Meanwhile, secondary data is obtained through the reviews literature of previous studies and other literature and legislation. The results of this research show that the protection of child victims of violent acts in Sumbawa district has not walked the maximum, some of the obstacles are maintenance of child protection has not been a priority program of local governments, yet The availability of safe houses and human Resources Limited in the agencies that provide services and assistance for victims.